Pelatihan Menyusun Program Bimbingan Layanan dan Konseling Berdasarkan Asesmen Kebutuhan Siswa pada Guru BK - Aini, Farida (Devotion : Jurnal Pengabdian Psikologi, 2022)
Abstract: This community service activity throughout training has the aim to increase the ability of counseling teachers at SMA Penggerak in making Guidance and Counseling program based on an assessment of student needs to support the implementation of Kurikulum Merdeka. The implementation of the Kurikulum Merdeka, especially at SMA Penggerak has its own peculiarity because students can choose subject according to their interests with the guidance of a counseling teacher. This training was based on Experiential Learning Theory (ELT) approach for adult learner. The training involved facilitator whose selected persons through selection and had attended Technical Guidance. Most of facilitators were psychologist from all regions in Indonesia. The training is conducted online using Google Meet simultaneously for all counseling teachers of SMA Penggerak in 7 (seven) Provinces. Moreover, participants in this article came from 4 (four) provinces on the island of Sulawesi. The training was held for two days with a total of 10 JP (Lesson Hours). The training was attended by 20 participants. The results of the training showed that counseling teachers were able to design the Guidance and Counseling program based on an assessment of student needs and presented it at the end of the training.